2018
DOI: 10.3389/fphar.2018.01074
|View full text |Cite
|
Sign up to set email alerts
|

Development and Role in Therapy of Canakinumab in Adult-Onset Still’s Disease

Abstract: Adult-onset Still’s disease (AOSD) is a rare inflammatory disease of unknown etiology typically characterized by episodes of spiking fever, evanescent rash, arthralgia, leukocytosis, and hyperferritinemia. The pivotal role of interleukin (IL)-1 and other pro-inflammatory cytokines gives rise to the development of new targeted therapies. Currently, AOSD patients can benefit from efficient and well tolerated biologic agents, such as IL-1, IL-6, and tumour necrosis factor (TNF)-α antagonists. Canakinumab, a human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
0
13
0
1
Order By: Relevance
“…These reports demonstrate that canakinumab is effective even in these difficult-to-treat patients who are likely to have more severe disease. Based on our systematic review of the literature and on the most recent review by Galozzi and colleagues [20], there are only 24 published cases of patients with AOSD who were treated with canakinumab. These reports show efficacy in reducing both systemic and articular manifestations, while reducing the need for corticosteroids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports demonstrate that canakinumab is effective even in these difficult-to-treat patients who are likely to have more severe disease. Based on our systematic review of the literature and on the most recent review by Galozzi and colleagues [20], there are only 24 published cases of patients with AOSD who were treated with canakinumab. These reports show efficacy in reducing both systemic and articular manifestations, while reducing the need for corticosteroids.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, there is only one randomized controlled trial (RCT) on the use of anakinra in patients with AOSD [18], and data supporting the efficacy/safety of canakinumab are only available from two RCTs performed in patients with SJIA [19]. Based on the similarities with SJIA, the European Medicines Agency (EMA) has now approved the use of canakinumab in patients with AOSD [20]. To address the lack of evidence-based guidance on the management of AOSD, a panel of ten Italian physicians with expertise in the management of Still’s disease convened a meeting in January 2018 with the goal of addressing unresolved issues and reaching consensus about the management of patients with AOSD using IL-1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…With an incidence of 0.16-0.62 per 100,000 population worldwide, adult-onset Still's disease (AOSD) is a rare multisystem inflammatory disease that usually affects young adults (1). Although the exact pathogenesis behind AOSD remains unknown, a combination of genetic and environmental factors seems to be involved (2).…”
Section: Introductionmentioning
confidence: 99%
“…The available data indicate that canakinumab is effective and well tolerated for treating AOSD. 45 , 47 49 , 110 , 142 , 143 A study has shown that treatment of adult patients with AOSD and active joint involvement with canakinumab led to a clinically significant improvement of outcome measures including DAS28-ESR, DAS28-CRP, ACR30, ACR50 and ACR70 and remission, compared with placebo. It was difficult to complete the recruitment of this trial due to the rarity and severity of the disease as well as the conditional approval of canakinumab for AOSD by the EMA; therefore, the study was terminated prematurely.…”
Section: Adult Onset Still’s Diseasementioning
confidence: 99%